The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1161/01.cir.54.6.862
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of left ventricular function by radiographic techniques.

Abstract: since these initial contributions to quantitative angiocardiography, the principles and techniques have remained generally unchanged and are testimony to the clear understanding of ventricular dynamics shown by these investigators. Biplane radiographic equipment and filming devices, direct manual measurements from the ventriculogram, geometric assumptions, and extensive mathematical calculations were basic to these methods for estimation of left ventricular volume. The studies of Arvidsson and Dodge were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

1980
1980
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(15 citation statements)
references
References 148 publications
0
12
0
3
Order By: Relevance
“…The differences between the Valanis-Landel and Rivlin-Saunders predictions also illustrate the limitations of the common practice (Glantz, 1976;Rackley, 1976;Fester and Samet, 1974;Mirsky and Parmley, 1973;Lafferty et al, 1972;Diamond et al, 1971) of attempting to deduce myocardial stressstretch behavior from observed LV P-V behavior. Just as two (or more) stress-stretch relations can have virtually the same uniaxial stress-stretch behavior but lead to very different P-V and P-S relations, so too can many stress-stretch relations lead to the same P-V behavior but have very dissimilar uniaxial stress-stretch behavior and lead to different P-S relations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The differences between the Valanis-Landel and Rivlin-Saunders predictions also illustrate the limitations of the common practice (Glantz, 1976;Rackley, 1976;Fester and Samet, 1974;Mirsky and Parmley, 1973;Lafferty et al, 1972;Diamond et al, 1971) of attempting to deduce myocardial stressstretch behavior from observed LV P-V behavior. Just as two (or more) stress-stretch relations can have virtually the same uniaxial stress-stretch behavior but lead to very different P-V and P-S relations, so too can many stress-stretch relations lead to the same P-V behavior but have very dissimilar uniaxial stress-stretch behavior and lead to different P-S relations.…”
Section: Discussionmentioning
confidence: 92%
“…This interrelationship is a mathematical model which is used to predict wall stress from observed pressure and geometry (Ford, 1976;Rackley, 1976;Mirsky, 1974;Spotnitz and Sonnenblick, 1973;Streeter andHanna, 1973a, Gould et al, 1972;Falsetti, et al, 1970Falsetti, et al, ,1971Burns et al, 1971) and stressstrain relations for myocardial tissue from either LV pressure-volume behavior (Glantz, 1976;Rackley, 1976;Fester and Samet, 1974;Mirsky and Parmley, 1973;Lafferty et al, 1972;Diamond et al, 1971), or stress-strain relations of papillary muscle. It also is used to assess myocardial contractility (Falsetti et al, 1971;Hugenholtz et al, 1970) and predict LV volume from pressure (Burns et al, 1971) or vice versa (Sonnenblick and Strobeck, 1977).…”
Section: The Law Of Laplacementioning
confidence: 99%
“…Other investigators using Doppler methods have suggested reduced diastolic cerebral blood flow velocity in premature infants with patent ductus arteriosus.37 These observations are consistent with our finding of significantly decreased cerebral blood flow in the lambs before occlusion of the ductus arteriosus. The association of cerebral ischemia and cerebral hemorrhage has been well documented in the premature infant.38 19 The contribution of cerebral hypoperfusion or ischemia secondary to left-to-right ductal shunting in the pathogenesis of cerebral hemorrhage remains to be evaluated. 39 The mechanical and autoregulatory factors that influence the quantity and distribution of coronary blood flow are complex.40-3 The increased myocardial blood flow after occlusion of the ductus arteriosus was most likely associated with a diminished coronary vascular "resistance," for transcoronary perfusion pressure changed minimally.42 43 Furthermore, the rate-pressure product, which correlates well with instantaneous myocardial oxygen consumption (MVO2) in sheep and newborn lambs, did not change after occlusion (table 1, fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen patients received nifedipine and 13 received placebo. No change occurred in any variable after placebo.…”
mentioning
confidence: 99%